Senyawa Phenolik Akar Pisang CV. Kepok (Musa acuminata) yang Diinduksi dengan Fungi Mikoriza Arbuskular Indigenus PU10-Glomus sp 1 terhadap Penyakit Darah Bakteri - Suswati, Suswati; Habazar, Trimurti; Husin, Eti Farda; Nasir, Nasril; Putra, Dedi Prima; Taylor, Peter (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
Cooking banana (Musa acuminata) cv. Kepok is the most susceptible to Blood disease bacterium (BDB) infection.From previous study revealed the best isolate indigenous Arbuscular Mycorrhiza Fungi-Pasar Usang 10 (PU10-Glomus sp 1) could induce cv.Kepok resistance to BDB in green house and field experiment. The AMF could changethe phenolic compound in root plant. This objectives were to measure the root phenolic compound and bioassayto BDB. The 50 grams fresh inoculant PU10-Glomus sp 1 were applicated to banana root plants 60 days old with 6levels time course: 12; 24; 36; 48; 72; 92 hours and control (without PU10-Glomus sp 1). The root methanolicextraction followed to Echeverri et al., (2002) methode with vacuum concentration of the filtrate and partitioninginto ethyl acetate revealed the presence of an antibacterial compound as detected by TLC (Thin LayerChromatography), assay phenolic contained by Spectrofotometer UV-Vis 1700. PharmaSpec. Shimadzu andbioassay using BDB. Nine antibacterial compounds rose from root banana seedling colonized by PU10-Glomus sp1 in 12 hours after applicated (haa) ; 24; 36 and 48 haa. They were with Rf values of 0.16; 0.17; 0.19; 0.26; 0.32; 0.37;0.71; 0.80 and 0.83 on silica plates run in hexane:ethyl acetate (1:2 v/v) and control contained only 0.05 and 0.28.These compounds produced fluorescens which was bright yellow green spots and purple and have antimicbrobialproperties to BDB.